The Effect of Online Tutorial Availability and Tax Knowledge Level on Satisfaction in Using Coretax (Case Study of MSMEs in Medan Petisah District) - Hermawan Sutanto; Latersia Br Gurusinga; Angelica Angelica (SEAN Institute, 2026)
The purpose of this study is to determine and analyze the influence of the Availability of Online Tutorials and the Level of Tax Knowledge on Coretax User Satisfaction (A Case Study of MSMEs in Medan Petisah District). The research method used in this study is quantitative research. The population in this study consisted of 233 respondents, while the sample was determined using the Slovin formula, resulting in 147 samples. The results of the study indicate that partially, the Availability of Online Tutorials has a positive and significant effect on Coretax User Satisfaction. The Level of Tax Knowledge also has a positive and significant effect on Coretax User Satisfaction. Simultaneously, the Availability of Online Tutorials and the Level of Tax Knowledge have a positive and significant effect on Coretax User Satisfaction.